Montenegro : Technical Assistance Report-External Sector Statistics. (IMF Staff Country Reports; Country Report, 2022)
The International Monetary Fund (IMF)'s Statistics Department (STA) conducted a technical assistance (TA) mission to the Central Bank of Montenegro (CBM) for the compilation of external sector statistics (ESS) during April 28-May 13, 2021. The mission was funded by Eurostat to meet the European Union (EU)'s acquis1 from the ESS perspective. The mission focused on the compilation of quarterly international investment position (IIP),2 and assisted the CBM in preparing the Reserves Data Template (RDT) as well as in recording of financial intermediary services indirectly measured (FISIM) in balance of payments statistics.